Case Report: SARS-CoV-2 Infection in a Child With Suprasellar Tumor and Hypothalamic-Pituitary Failure - Gaudino, Rossella; Orlandi, Valentina; Cavarzere, Paolo; Chinello, Matteo; Antoniazzi, Franco; Cesaro, Simone; Piacentini, Giorgio (Frontiers in Endocrinology, 2021)
In early 2020, a novel coronavirus leading to potentially death was discovered. Since then, the 2019 coronavirus disease (COVID-19) has spread to become a worldwide pandemic. Beyond the risks strictly related to the infection, concerns have been expressed for the endocrinological impact that COVID-19 may have, especially in vulnerable individuals with pre-existing endocrinological health conditions. To date new information is emerging regarding severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) in children but the literature is still scarce concerning this infection in patients with intracranial malignant neoplasms. We report a 9-year-old child infected with SARS-CoV-2 and recent diagnosis of suprasellar non-germinomatous germ cell tumor also suffering from diabetes insipidus and hypothalamic-pituitary failure (hypothyroidism, adrenal insufficiency, hypothalamic obesity and growth hormone deficiency) and its clinical course. The patient remained asymptomatic for the duration of the infection without requiring any change in the replacement therapeutic dosages taken before the infection. We then discuss the proposed approach to treat a pediatric patient with SARS-CoV-2 infection and hypothalamic-pituitary failure and we include a review of the literature. Our report suggests that SARS-CoV-2 infection is usually mild and self-limiting in children even those immunocompromised and with multiple endocrinological deficits. Patients are advised to keep any scheduled appointments unless informed otherwise.